2012
DOI: 10.1007/jhep11(2012)116
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum structure and stability of a singlet fermion dark matter model with a singlet scalar messenger

Abstract: Abstract:We consider the issue of vacuum stability and triviality bound of the singlet extension of the Standard Model (SM) with a singlet fermion dark matter (DM). In this model, the singlet scalar plays the role of a messenger between the SM sector and the dark matter sector. This model has two Higgs-like scalar bosons, and is consistent with all the data on electroweak precision tests, thermal relic density of DM and its direct detection constraints. We show that this model is stable without hitting Landau … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
125
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 111 publications
(127 citation statements)
references
References 61 publications
1
125
0
1
Order By: Relevance
“…Even if we relax the assumption of the local dark gauge symmetry and consider more phenomenological Higgs-portal DM models, there will still appear a singlet scalar boson that can mix with the SM Higgs boson, if the Higgs-portal DM is a singlet Dirac fermion [28,29] or a vector boson [16,30,31]. Also, it can play an important role in DM phenomenology.…”
Section: Dark Matter Models With Dark Gauge Symmetries And/or Higgs Pmentioning
confidence: 99%
See 1 more Smart Citation
“…Even if we relax the assumption of the local dark gauge symmetry and consider more phenomenological Higgs-portal DM models, there will still appear a singlet scalar boson that can mix with the SM Higgs boson, if the Higgs-portal DM is a singlet Dirac fermion [28,29] or a vector boson [16,30,31]. Also, it can play an important role in DM phenomenology.…”
Section: Dark Matter Models With Dark Gauge Symmetries And/or Higgs Pmentioning
confidence: 99%
“…• The additional singlet scalar boson can improve the stability of EW vacuum up to the Planck scale [29].…”
Section: Jhep10(2015)057mentioning
confidence: 99%
“…Since the stability condition of the electroweak vacuum is strongly sensitive to new physics, from the phenomenological point of view it is clear that beyond SM physics models have to pass a sort of "stability test" [21][22][23]. Indeed, only new physics models that reinforce the requirement of a stable or metastable (but with τ > T U ) electroweak vacuum can be accepted as a viable UV completion of the SM [24][25][26][27][28][29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in Refs. [52][53][54], the authors demonstrated that the effective Lagrangian approaches based on the unbroken subgroup (SU (3) C ×U (1) Y ) of the SM gauge group produce erroneous results, especially on the direct detection cross section through the Higgs couplings to the dark matter particles. In the renormalizable versions of hidden sector (or Higgs-portal) DM models with the full SM gauge group (SU (3) c × SU (2) L × U (1) Y ), one always have an extra singlet scalar s which couples to the hidden sector DM particles at renormalizable level.…”
Section: Introductionmentioning
confidence: 99%
“…And the mixing of this singlet scalar s with the SM Higgs h thermalize the hidden sector DMs. Due to the mixing between the h and s, there are always at least two neutral Higgslike scalar bosons, which are mixtures of the SM Higgs h (remnant of the SU (2) L doublet Higgs field) and a singlet scalar s. The singlet scalar s not only thermalizes the hidden sector DM efficiently, but also improves the stability of the EW vacuum up to Planck scale [53], unlike the SM case. It is important to realize that one can not integrate out the singlet scalar s simply assuming that s is very heavy.…”
Section: Introductionmentioning
confidence: 99%